Meningkatkan Keterampilan Berpikir Kritis Siswa Menggunakan Model Bambu Pada Muatan Matematika di Kelas V SDN Kuin Selatan 1 - Rahmad Khairinor; Ratna Purwanti (CV. ITTC INDONESIA, 2024)
The problem that occurred in this research was the less than optimal level of activity, critical thinking skills, and learning outcomes that students had when participating in mathematics learning. Things that cause these problems include teachers who do not apply learning models that are capable of developing students' understanding of the material when learning is carried out, teachers rarely use learning media when teaching, lack of student involvement in the learning process which means students are not trained to think critically. Efforts to deal with the problems that occur are by implementing the BAMBU model in learning. This research aims to describe changes that occur in teacher activities and student activities in learning, as well as analyzing changes in critical thinking skills and student learning outcomes which are the impact of learning activities on mathematics content building material. The research used is Classroom Action Research which consists of 3 meetings. The research subjects taken were 22 students in class V of SDN Kuin Selatan 1, which was carried out in the second semester of the 2023/2024 academic year. From the results of this research, it was found that the implementation of the teacher's activities succeeded in getting a score of 40 or the criteria